Exploring the needs of alternative curriculum among Bajau pupils in Semporna, Sabah - Tham, Jia Hao; Mustakim, Siti Salina; Mohd Sufian Kang, Enio Kang; Minghat, Asnul Dahar; Abdul Rahim, Abdul Hamid (Human Resource Management and Academic Research Society, 2022)
There is no way for pupils to fall behind in school. The difference in growth in these pupils’ lives will determine the future development of a nation. Bajau are an unidentified group of people who still live a maritime and nomadic lifestyle and have no access to formal education. They differ primarily in terms of socioeconomic status, place of residence, culture, historical origin, and citizenship. They have no chance of obtaining the government-provided education and spend their days on a boat or at the beach. This study is aimed to explore the needs of alternative curriculum among Bajau pupils in Semporna, Sabah. This research applied qualitative research by conducted focus group discussion with pupils from a national school in Semporna, Sabah. 15 pupils who meet the criteria as sample are purposely picked to participate in this research. All of the participants were able to express their perspectives and understanding. The data gathered demonstrated participants' enthusiasm for alternate curriculum. It is claimed that an entertaining alternative curriculum will entice students to attend school. As a result, there is an immediate need for us to create a fun learning alternative curriculum in order to reduce primary school dropout rates in Semporna, Sabah.